Pulmonate snails as marginalia in medieval and Renaissance manuscripts: a review of hypotheses - Monge, Julián (Universidad de Costa Rica, 2019)
Small drawings of armored knights fighting pulmonate snails have been found in several medieval and Renaissance manuscripts; and there are 26 hypothetical interpretations about what they mean. Manuscripts also depict fights between cartoonish humans, rabbits, monkeys, and several other real and imaginary animals, so they probably lack the deep meanings that many have imagined. More likely, these cartoons are simply comic relief based on the obvious similarity between humans and invertebrates that protect themselves with body armor.